Phylogeny of subclass Scuticociliatia（Protozoa,Ciliophora） using combined data inferred from genetic,morphological,and morphogenetic evidence - 伊珍珍 王艳刚 林晓凤 Khaled A. S. AL-RASHEID 宋微波 (Chinese journal of oceanology and limnology, 2010)
Gene sequence-based genealogies of scuticociliates are different from those produced by morphological analyses.For this reason,11 representative scuticociliates and two ambiguously related genera were chosen to test the ability of combined phylogenetic analyses using both gene sequences and morphological/morphogenetic characteristics.Analyses of both the SSrRNA gene sequences and the combined datasets revealed a consistent branching pattern.While the terminal branches and the order level relationships were generally well resolved,the family level relationships remain unresolved.However,two other trees based on ITS1-5.8S-ITS2 region sequences and morphological/morphogenetic characters showed limited information,due to a lack of informative sites in these two datasets.Our data suggest,however,that the combined analysis of morphological/morphogenetic characters and gene sequences did produce some changes to the phylogenetic estimates of this group.